Application of Compost Produced by Bioconversion of Coffee Husk by Black Soldier Fly Larvae (Hermetia Illucens) as Solid Fertilizer to Lettuce (Lactuca Sativa Var. Crispa): Impact to Growth - Rosmiati, Mia; Nurjanah, Katiana Apriyani; Suantika, Gede; Putra, Ramadhani Eka (Proceedings of the International Conference on Green Technology, 2017)
Lettuce is one of the most cultivated vegetables in West Java. Fertilizer plays important role for growth of this vegetables. Increasing cost of synthetic fertilizer and preference on less chemical residue agricultural products shifted the cultivation toward to application of more organic fertilizers. In this study, compost produced by bioconversion of coffee husk by black soldier fly larvae was applied as part of lettuce cultivation in order to observe the effect to growth. The result showed that lettuce cultivated with manure significantly produced highest plant height (20.37 ± 1.565 cm), number of leaves (12.20 ± 1.119), leaf area (129.45 ± 29.622 cm 2 ), and chlorophyl content (5.92 ± 1.227 mg/liter). On the other hand, lettuce cultivated with compost originated from bioconversion process showed second best value which is higher than value of conventional compost of coffee husk.